VIVENCIANDO OS DESAFIOS DO TRABALHO EM GRUPO - Denize Bouttelet Munari; Virgínia Faria Damásio; Michella F. B. Câmara (Universidade Federal de Goias, 1999)
The work in group is a reality in the daily of the nurses work, being lived in the whole period of your academic formation, however it is necessary to look for a larger reflection on that kind of work. We believed to be of extreme importance the referring studies to the grupal work while applied strategy in the Nursing attendance, so that we have more and more clear its foundations. Qualitative approach research developed with three groups of pregnant women that live in the periphery of Goiânia. We used for the collection of data the participant observation and written registrations. We verified along the development of the groups, that your objectives are reached in a more appropriate way when the members of the group take for itself the responsibility of turning a significant experience, tends the understanding of the importance of their participation. To work with the group and to live its path and them to be able to think about its movements is fundamental for us to apprehend co-ordinators of activities on the group, its difficulties and challenges. The theoretical-practical development, the reflection and the concrete experience in the grupal work, makes possible for us to affirm that it is a possible way to learn about the group and its benefits while strategy for the work in nursing attendance.